Spectroscopic observations and analysis of the unusual type Ia SN 1999ac - Garavini, G; Aldering, G; Amadon, A; Amanullah, R; Astier, P; Balland, C; Blanc, G; Conley, A; Dahlen, T; Deustua, SE; Ellis, R; Fabbro, S; et al. (2005)
We present optical spectra of the peculiar Type la supernova (SN Ia) 1999ac. The data extend from -15 to +42 days with respect to B-band maximum and reveal an event that is unusual in several respects. Prior to B-band maximum, the spectra resemble those of SN 1999aa, a slowly declining event, but possess stronger Si II and Ca II signatures (more characteristic of a spectroscopically normal SN). Spectra after the B-band maximum appear more normal. The expansion velocities inferred from the iron lines appear to be lower than average, whereas the expansion velocity inferred from calcium H and K are higher than average. The expansion velocities inferred from Si II are among the slowest ever observed, although SN 1999ac is not particularly dim. The analysis of the parameters v 10(Si II), R(Si II), v̇, and Δm 15 further underlines the unique characteristics of SN 1999ac. We find convincing evidence of C II λ6580 in the day - 15 spectrum with ejection velocity v > 16,000 km s -1, but this signature disappears by day - 9. This rapid evolution at early times highlights the importance of extremely early-time spectroscopy. © 2005. The American Astronomical Society. All rights reserved.